Peculiarities and functioning of obsolete lexis in Pushkin’s tales (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2012)
The publication studies the main characteristics of the archaisms as the type of the obsolete lexis based on the material from Pushkin’s tales, where this material is determined in agreement with the lexical and semantic type of archaisms and with stylistic in the vocabulary of literature. We also analyze archaistic grammatical forms.
Keywords: archaisms; Old Slavonic and Old Russian lexis; lexical meaning; means of stylization